2017
DOI: 10.18273/revion.v30n1-2017007
|View full text |Cite
|
Sign up to set email alerts
|

Producción de Ácidos Grasos Poliinsaturados a partir de Biomasa Microalgal en un Cultivo Heterotrófico

Abstract: ResumenEl trabajo aquí presentado se enfocó en la producción de ácidos grasos poliinsaturados o PUFA's (por sus siglas del inglés PolyUnsaturated Fatty Acids) a partir de biomasa microalgal en un cultivo heterotrófico. Para esto, se utilizaron las algas Chlorella sp. y Scenedesmus sp., en condiciones heterotróficas, posteriormente se seleccionó la cepa con mayor productividad, se realizaron las cinéticas con ambas algas para cuantificar la concentración de biomasa, glucosa, nitrógeno y fósforo; se extrajeron l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…has the ability to assimilate organic substances present in wastewater. Several authors have shown that microalgae of the Chlorophyta division have the ability to assimilate organic substrates and grow in mixotrophic or heterotrophic conditions [LEAL MEDINA et al 2017]. In a similar vein, cultivation conditions influence biomass production and accumulation of metabolites.…”
Section: Biomass Production and Removal Of Cod Nitrates And Phosphatesmentioning
confidence: 97%

Journal of Water and Land Development

Urbina-Suarez,
Barajas-Solano,
Garcia-Martinez
et al. 2022
“…has the ability to assimilate organic substances present in wastewater. Several authors have shown that microalgae of the Chlorophyta division have the ability to assimilate organic substrates and grow in mixotrophic or heterotrophic conditions [LEAL MEDINA et al 2017]. In a similar vein, cultivation conditions influence biomass production and accumulation of metabolites.…”
Section: Biomass Production and Removal Of Cod Nitrates And Phosphatesmentioning
confidence: 97%

Journal of Water and Land Development

Urbina-Suarez,
Barajas-Solano,
Garcia-Martinez
et al. 2022
“…The results establish that chemostats and fed-batch reactors produce similar quantities of lipids [ 141 ]. Likewise, some experiments using continuously stirred tank reactors (CSTR) for PUFA production have given good results [ 142 ].…”
Section: Production Systemsmentioning
confidence: 99%
“…Polyunsaturated fatty acids Oleic acid was the major fatty acid present (28.75%). [131] Scenedesmus sp. Carotenoids C:N ratio affected biomass and carotenoid production.…”
Section: Botryococcus Braunii Fatty Acids and Exopolysaccharidesmentioning
confidence: 99%